EPISTEMOLOGI MANHAJ TARJIH DAN POLA PIKIR MATEMATIKA: SINERGI LOGIKA DALAM TRANSFORMASI PENDIDIKAN ISLAM BERKEMAJUAN - Nanik Tri Purwaningsih; Mhd. Lailan Arqam (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This research aims to comprehensively examine the alignment between Muhammadiyah's Manhaj Tarjih logic and mathematical thinking, alongside its implications for education, humanization, and enlightenment dawah. Employing a qualitative approach through library research, data were gathered from primary sources, including official organizational documents, educational philosophy literature, and relevant national and international scientific journals. The analysis was conducted using inductive and reflective content and thematic analysis to achieve a holistic understanding. The findings reveal a robust epistemological alignment between Manhaj Tarjih logic and mathematical reasoning, particularly regarding rationality, systematic structure, and consistency. Furthermore, mathematics education serves a strategic role in integrating Muhammadiyah’s scientific mission, fostering humanistic awareness, and internalizing Islamic values into pedagogical practices. This study concludes that mathematics is an essential medium for developing progressive Islamic education that is critical, rational, and welfare-oriented. Ultimately, this synergy strengthens the enlightenment dawah movement, ensuring it remains adaptive to modern scientific dynamics while staying firmly rooted in humanistic principles and religious values.